Prevalence and predictors of perceived disrespectful maternity care in postpartum Iranian women: a cross-sectional study - Khadije Hajizadeh; Maryam Vaezi; Shahla Meedya; Sakineh Mohammad Alizadeh Charandabi; Mojgan Mirghafourvand (BMC, 2020)
Abstract Background Disrespectful maternity care is a key impediment to achieving a good quality care. Identifying predicting factors can be used in mitigating any potential risk in for disrespect and abuse in maternity care. The present study was conducted to determine prevalence and predictors of perceived disrespectful maternity care among Iranian women. Methods A cross-sectional study was conducted in three public and three private hospitals in the city of Tabriz involving 334 postpartum women. Tools included socio-demographic, pregnancy, labour and birth characteristics questionnaires, and disrespect and abuse scales. Data were collected in 6 to 18 h after birth. Multivariate logistic regression was used to determine predictors of disrespectful maternity care. Results A majority of the women (253; 75.7%) reported one or several types of perceived disrespectful maternity care. The most frequent types related to not allowing women to choose labour positions (142; 44.3%) and not allowing them to move during labour (148; 42.5%). Nighttime childbirth (aOR 3.07; 95% CI 1.61 to 5.88) increased the likelihood of perceived disrespectful maternity care. However, presence of spouses to accompany their wives in waiting rooms (aOR 0.32; 95% CI 0.11 to 0.88), the attendance of private physicians (aOR 0.05; 95% CI 0.02 to 0.12), and midwives (aOR 0.22; 95% CI 0.11 to 0.45) decreased the likelihood of perceived disrespectful maternity care. Conclusion The results showed high levels of perceived disrespectful maternity care in postpartum women. Therefore, appropriate interventions, such as encouraging spouses' presence, increasing the number of night shift staff, and training obstetric residents and midwives by holding ethics classes, with particular emphasis on empathy with patients.